Efficacy and Safety of Lenvatinib Plus Programmed Death-1 Inhibitors with or Without Transarterial Chemoembolization in the Treatment of Unresectable Hepatocellular Carcinoma - Jin M; Jiang ZQ; Qin JH; Qin HX; Jiang KW; Ya HX; Gu J; Gui MR; Li YH; Xu LK; Fu HX; Xiao XH; et al. (Journal of Hepatocellular Carcinoma)
Ming Jin,1,* Zhi-qing Jiang,2,* Jia-hui Qin,3,* Hui-xia Qin,4,* Kai-wen Jiang,3,* Hou-xiang Ya,3 Jing Gu,3 Mo-rui Gui,5 Yao-hua Li,3 Long-kuan Xu,6 Hai-xiao Fu,6 Xu-hua Xiao,7 Shu-qun Li3 1Department of Vascular Intervention, Affiliated Hospital of Guilin Medical University, Guilin, Guangxi, People’s Republic of China; 2Department of Gastrointestinal Surgery, Affiliated Hospital of Guilin Medical University, Guilin, Guangxi, People’s Republic of China; 3Department of Hepatobiliary Pancreatic Surgery, Affiliated Hospital of Guilin Medical University, Guilin, Guangxi, People’s Republic of China; 4Interventional Center, Affiliated Hospital of Guilin Medical University, Guilin, Guangxi, People’s Republic of China; 5Department of Burn Wound Repair and Plastic Surgery, Medical Aesthetic Surgery, Affiliated Hospital of Guilin Medical University, Guilin, Guangxi, People’s Republic of China; 6Department of Pathology, Affiliated Hospital of Guilin Medical University, Guilin, Guangxi, People’s Republic of China; 7Department of Gastroenterology, Affiliated Hospital of Guilin Medical University, Guilin, Guangxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shu-qun Li, Email lishuqun2008@126.comPurpose: Transarterial chemoembolization (TACE) is recommended as a standard therapy for intermediate-stage hepatocellular carcinoma (HCC) and is the most widely used first-line treatment for advanced HCC. This study aimed to evaluate the clinical benefits and tolerability of TACE added to a combination of lenvatinib and programmed death-1 (PD-1) inhibitor in patients with unresectable HCC (uHCC).Patients and Methods: We conducted a retrospective cohort study involving 144 patients with uHCC treated between August 2020 and August 2023. Patients received a combination of lenvatinib and a PD-1 inhibitor with or without TACE (T+L+P, n=81 or L+P, n=63, respectively). The baseline characteristics of the two groups were compared, and propensity score matching (PSM) was used to minimize bias. The study endpoints included overall survival (OS), progression-free survival (PFS), and objective response rate (ORR). Factors influencing survival rates were analyzed using Cox regression, and adverse events (AEs) were documented and assessed.Results: Before PSM, the T+L+P group showed significantly higher ORR (64.1% vs 44.4%, p < 0.05), longer median PFS (14.3 vs 9.6 months, p < 0.05), and longer median OS (24.6 vs 19.5 months, p < 0.05) compared to the L+P group. Even post-PSM, the T+L+P group showed significantly better OS and PFS compared to the L+P group (mOS: 28.0 vs 17.6 months p=0.0011, mPFS: 15.8 vs 9.3 months, p < 0.05). Univariate and multivariate analyses identified treatment options as independent factors for PFS and OS. The safety profile of the T+L+P regimen was acceptableThe incidence and severity of adverse reactions in the T+L+P group were not significantly different compared to the L+P group (any grade, 90.1 vs 93.6%, p=0.551; grade≥ 3, 25.9 vs 23.8%, p=0.843).Keywords: unresectable hepatocellular carcinoma, lenvatinib, transarterial chemoembolization, PD-1 inhibitor, combination therapy, propensity score matching